Liderança transformacional na educação básica jesuíta: diretrizes para a formação de educadores da segurança no Colégio Anchieta - RS - Santos, José Ildo dos (Universidade do Vale do Rio dos Sinos, 2025)
This research aimed to structure key axes and general action guidelines for developing a dissemination plan of the transformational leadership model among security educators at Colégio Anchieta – Jesuit Education Network – Porto Alegre. Grounded in the concept of leadership, with emphasis on transformational leadership, the study highlights collaborative participation and shared responsibility in collective processes, promoting influential actions beyond mere task assignment or commandand-control logic. A mixed-methods approach was adopted, combining quantitative and qualitative data collection through questionnaires administered to security educators and a focus group conducted with the school’s leadership team. The findings suggest that, through structured actions such as discussion circles, informal dialogue sessions ("mate papo"), and ongoing professional development, it is possible to foster systemic thinking and coordinated work. These initiatives align with the transformational leadership model by encouraging identification, engagement, and availability among team members.
Keywords: Educadores da segurança; Liderança; Liderança transformacional; Security educators; Leadership; Transformational leadership